Practical App Development with Aurelia Leverage the Power of Aurelia to Build Personal and Business Applications - Duffield, Matthew (Apress, 2018)
Explore all the aspects of the Aurelia framework, including routing, templating, data binding, custom elements, event aggregation, HTTP services, features, plugins, etc. You'll see how to tie all the pieces together and walk away with an understanding of how to build applications, end to end. Practical App Development with Aurelia teaches you to write a line of business applications using simple, clean JavaScript harnessing the Aurelia framework. You'll learn the key abstractions of Aurelia and understand the life cycle of components. If you want to understand the key features of the framework and gain a mastery of building Aurelia apps, then this is the book for you. Aurelia is a modern front-end framework for mobile, desktop, and web clients. It is standards-based meaning that it has a very low learning curve. This book highlights the framework's simplicity and its power.